United Kingdom : projected level of demand, supply, and imports of farm products in 1965 and 1975 - Economic Research Service; Foreign Agricultural Service (Washington, D.C. : U.S. Department of Agriculture, 1962)
The aim of presenting these forecasts is to show a reasonable expectation of a normal state of supply, demand and imports.
osc 21/05/2019
Loans
Keywords: Agricultural economics; United Kingdom